1996
DOI: 10.1037/0022-006x.64.4.660
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the psychopharmacology of anxiety disorders.

Abstract: Anxiety disorders are the most prevalent mental disorders in the United States. In the past 3 decades, substantial advances have been made in the ability to identify and treat anxiety disorders including panic disorder (PD), social phobia (SP), obsessive-compulsive disorder (OCD), generalized anxiety disorder (GAD), and posttraumatic stress disorder (PTSD). It is now known that these common, usually chronic disorders confer significant disability to untreated sufferers. This overview highlights some of the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 43 publications
(55 reference statements)
1
58
0
1
Order By: Relevance
“…Problems with sedation, abuse, tolerance, dependence/ withdrawal, as well as cognitive impairment, are causes of concern with the use of benzodiazepines (Shader and Greenblatt, 1993). Issues with longer onset of symptom relief (4-6 weeks) as well as side effects including nausea, insomnia, restlessness, agitation, weight gain, and sexual side effects are associated with the use of SSRIs as anxiolytics (Davidson et al, 1999;Lydiard et al, 1996). Similarly treatment with buspirone is also characterized by a delayed onset of anxiolytic activity as well as gastrointestinal side effects (Rakel, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Problems with sedation, abuse, tolerance, dependence/ withdrawal, as well as cognitive impairment, are causes of concern with the use of benzodiazepines (Shader and Greenblatt, 1993). Issues with longer onset of symptom relief (4-6 weeks) as well as side effects including nausea, insomnia, restlessness, agitation, weight gain, and sexual side effects are associated with the use of SSRIs as anxiolytics (Davidson et al, 1999;Lydiard et al, 1996). Similarly treatment with buspirone is also characterized by a delayed onset of anxiolytic activity as well as gastrointestinal side effects (Rakel, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Costs of psychotropic medications have increased 17% annually, far outpacing other mental health expenditures and spending increases on medications overall (15,16). Newer agents with potentially greater tolerability are widely available (16)(17)(18), making anti-depressants among the most widely prescribed classes of medications in most health care systems (19,20).…”
mentioning
confidence: 99%
“…36,37 Cognitive-behavioral therapy and medication CBT is an excellent choice as a first-line treatment. It has good acceptability to patients, 13,17,38 a relatively fast onset of action, 39 strong acute efficacy and strong maintenance of treatment gains, 10,16 and strong cost-efficacy. 40 There is also evidence that CBT can be effective for PD patients refractory to drug treatment (i.e., failure to respond adequately following treatment with the recommended dose and duration of pharmacotherapy, or intolerance to higher dose).…”
Section: Dependence On Relativesmentioning
confidence: 99%
“…15 Cognitive-behavioral therapy (CBT) for PD is a therapeutic alternative that has good short-and long-term response for both core panic symptoms as well as the residual and often persistent symptoms of anticipatory anxiety, phobic avoidance, and agoraphobia. 10,11,13,16 Studies have confirmed that CBT can change PD course not only for preventing relapses, but also because it prolongs the time interval between them. 17,18 Brief treatment (often in the range of 12 sessions) with CBT is associated with high (75%) panic free rates among patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation